Rotational osteoplasty and bioabsorbable polylactate pin fixation in Pipkin type 2 fracture with acute osteochondral defect: a case report - Maluta, Tommaso; Micheloni, Gian Mario; Sandri, Andrea; Regis, Dario; Costanzo, Alessandro; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
Pipkin fractures are relative rare high-energy lesions characterized by an intra-articular fracture of the femoral head after posterior hip dislocation. Early anatomic reduction and stable fixation are the main goals of treatment. This case evaluates the outcome of managing Pipkin type 2 fracture with acute osteochondral defect of the femoral head using “rotational osteoplasty” and bioabsorbable polylactate pin fixation. 24-year-old male patient was involved in a motorcycle accident, suffering from a left hip fracture-dislocation, and pelvic Computed Tomography revealed a Pipkin type 2 lesion. An open urgent treatment was performed. After  anatomic reduction of the femoral head fragment a large osteochondral defect in the anterior-superior weight bearing surface was evident. The pattern of the fracture allowed us to perform a “rotational osteoplasty” including rotation of the femoral head fragment, to obtain an osteochondral cartilage congruence of the anterior-superior surface. Stable fixation was obtained by three bioabsorbable polylactate pins. At four-year follow up the patient had an excellent outcome and Magnetic Resonance Imaging (MRI) showed fracture healing, minimal signs of arthritis, excluding osteonecrosis of the femoral head. The reported case confirms that Pipkin fractures are very insidious surgical urgencies. In selected cases, “rotational osteoplasty” may be an alternative to osteochondral transplant for acute osteochondral defect of the femoral head. Bioabsorbable polylactate pin fixation allowed us to have a stable fixation evaluating the bone healing process and vitality of femoral head by MRI.